Antimicrobial Resistance (AMR). Reflections after SADI’s First National Conference to Combat AMR (Actualizaciones en Sida e Infectología, 2024)
Since 2015, every June 21, the National Day for the Responsible Use of Antibiotics is celebrated in Argentina. That day was chosen because the onset of winter marks the beginning of the period when most antimicrobials are used, in all regions, due to acute respiratory infections.This date was set by a Joint Resolution (834/15 and 391/15) of the National Ministries of Health and Agriculture, Livestock and Fisheries, highlighting the fact that the problem of antimicrobial use and its inevitable consequence, antimicrobial resistance (AMR), is an issue that not only concerns human medicine but also areas such as agricultural and livestock production, veterinary medicine and the environment.In 2022, Argentina passed Law 27680, becoming a pioneer in the prevention and control of antimicrobial resistance in the region. It declares "of national public interest the prevention and control of AMR" and establishes the need for the creation of a National Action Plan for the Prevention and Control of AMR and Healthcare-Associated Infections (HAI). The body of the law highlights the ideas of strengthening surveillance of AMR as well as HAIs based on the "One Health" model, promoting the appropriate use of and equitable access to antimicrobials, and raising awareness, informing and educating about AMR and HAIs. On the other hand, the creation of the National Commission for the Control of AMR (CoNaCRA) is considered and its functions include promoting the incorporation in the curricula of undergraduate and graduate university courses in health sciences and in those related to the healthcare, veterinary, environmental and agricultural practice sectors, of the necessary contents for the correct interpretation, assessment and approach to the problem of AMR in accordance with the "One Health" strategy and the prevention, surveillance and control of HAIs. This sentence highlights the idea that the problem is not only related to human medicine -both its determinants and its consequences- but that it is a complex environmental issue that requires a "One Health" approach and emphasizes the truly inescapable value of education in order to achieve social goals.On June 28th, the Argentine Society of Infectious Diseases (SADI) held the First National Conference to Combat AMR in the auditorium of the School of Medicine of the University of Buenos Aires under the slogan "From the classroom to the community: educating for action".The event had an enriching scientific program. Prestigious physicians and veterinarians, pharmacists, infection control nurses and biochemists graced the session, allowing a truly cross-cutting approach to the problem, while various scientific societies, professional associations and associated government agencies collaborated actively.Relevant data were presented during the event.A cross-sectional study carried out in intensive care units of 164 hospitals in 21 provinces showed that 51.9% of patients had an infection and, of these, 29.3% were caused by multidrug-resistant microorganisms, with a mortality rate of 27.1% (1).The EMBARC-AR study, which analyzed carbapenem-resistant Gram-negative bacilli bacteremias in 34 hospitals in Argentina during 2022, showed that 48% of the strains produced carbapenemase type MBL: a mechanism that drastically limits the therapeutic arsenal and was associated with a 30-day mortality rate of 41% (2).These worrying data contrast with the hopeful reality that both studies were carried out by the joint effort of SADI, the Argentine Society of Intensive Care and the National Reference Laboratory ANLIS/Malbrán, evidencing the fact that there are many wills trying to study the local reality of AMR and searching for information that will allow combating it effectively.The interaction between AMR in human health and the environment becomes indisputable when considering that sea lions and a humpback whale were found in the coast of Buenos Aires, carrying E. coli with ESBLs (3). As proposed by the law, the approach to the problem of AMR should be based on the concept of "One Health".A survey among 551 advanced medical students from 12 provinces showed that topics such as infection control and culture sampling were topics that students felt they had insufficiently addressed during their studies. Similarly, only 37% of the students said they had worked, in some way, on the concept of antibiotic treatment shortening and only 28% on the concept of "One Health" during their studies, while almost 50% found no relationship between prescribing antibiotics in situations in which they are unnecessary and AMR.The same survey showed that nearly 90% of students use digital media to supplement their learning, but only 56% mentioned that this type of support was used frequently in their universities.Undoubtedly, the challenge presented to us by the coming generations is huge, and the changes occurring in the teaching-learning process challenge us, but knowing the data provides a valuable input to start working.During the same day, the activity was replicated in 22 public and private universities in the country, where students discussed the contents produced.Within the framework of the conference, the "First Reflection Forum of Health Sciences University Teachers: How to Improve the Teaching of Antimicrobial Resistance" was held. Medical professors from 11 public and private universities of the Metropolitan Area of Buenos Aires (AMBA) participated in the meeting and discussed aspects of the curriculum, contents, approach and technologies, enriching the knowledge of each participant and producing conclusions that will be included in a document for dissemination.While it is not yet 100 years since the discovery of penicillin, bacteria have been reproducing in different ecosystems for 3.8 billion years, at extremely high speed and accumulating learning and resistance mechanisms that, in many cases, precede the discovery of antibiotic molecules. Undoubtedly, we must be very smart to face such a competitive advantage, in pursuit of health and with deep respect for the environment.The challenge of AMR is of concern to all of us, and from SADI we are making a minimum contribution that, we hope, will be replicated and multiplied. The conference's slogan was "educating for action". We are convinced that the effort is great but the goal is well worth it.
Keywords: AMR; Conference